2012
DOI: 10.1029/2012wr012008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sound attenuation by suspended sediment on ADCP backscatter calibrations

Abstract: [1] Although designed for velocity measurements, acoustic Doppler current profilers (ADCPs) are being widely used to monitor suspended particulate matter in rivers and in marine environments. To quantify mass concentrations of suspended matter, ADCP backscatter is generally calibrated with in situ measurements. ADCP backscatter calibrations are often highly site specific and season dependent, which is typically attributed to the sensitivity of the acoustic response to the number of scatterers and their size. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 60 publications
0
75
0
1
Order By: Relevance
“…For instance, the residual transport of water in the Marsdiep has been estimated with models and observations before (Ridderinkhof 1988;Buijsman and Ridderinkhof 2007;Nauw et al 2014;Duran-Matute et al 2014), and large discrepancies between model and observations can be explained partly by the temporal and spatial limitations inherent to the ferry-borne ADCP measurements (Sassi et al subm.). Furthermore, given the typical uncertainties in the conversion from acoustical backscatter units to suspended sediment concentration (e.g., Sassi et al 2012), one may expect large deviations in long-term estimates.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the residual transport of water in the Marsdiep has been estimated with models and observations before (Ridderinkhof 1988;Buijsman and Ridderinkhof 2007;Nauw et al 2014;Duran-Matute et al 2014), and large discrepancies between model and observations can be explained partly by the temporal and spatial limitations inherent to the ferry-borne ADCP measurements (Sassi et al subm.). Furthermore, given the typical uncertainties in the conversion from acoustical backscatter units to suspended sediment concentration (e.g., Sassi et al 2012), one may expect large deviations in long-term estimates.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was repeated for different levels at each vertical. Details of the calibration procedure can be found in Sassi et al [2012b]. After calibration, spatiotemporal distributions of echo intensity measured with the shipborne ADCP were converted into SSC.…”
mentioning
confidence: 99%
“…Because ADCP is a surrogate method, the acoustic backscatter data collected still requires calibration using manual samples. Sassi et al (2012) have shown how this can be done efficiently. The resulting Q and SSC data may then be used to analyse hysteretic behaviour, which can indicate the relative contributions of proximal (e.g.…”
Section: Hydromorphological Data Collection and Analysismentioning
confidence: 99%